Combining Bayesian approaches and evolutionary techniques for the inference of breast cancer networks - Beretta, Stefano (2019)
Beretta, S., Castelli, M., Gonçalves, I., Merelli, I., & Ramazzotti, D. (2016). Combining Bayesian approaches and evolutionary techniques for the inference of breast cancer networks. In J. J. Merelo, J. M. Cadenas, F. Melicio, A. Dourado, A. Ruano, J. Filipe, & K. Madani (Eds.), ECTA 2016 - 8th International Conference on Evolutionary Computation Theory and Applications (pp. 217-224). (IJCCI 2016 - Proceedings of the 8th International Joint Conference on Computational Intelligence; Vol. 1). SciTePress. https://doi.org/10.5220/0006064102170224